Mean arterial pressure estimated by brachial pulse wave analysis and comparison with currently used algorithms - Grillo, Andrea; Salvi, Paolo; Furlanis, Giulia; Baldi, Corrado; Rovina, Matteo; Salvi, Lucia; Faini, Andrea; Bilo, Grzegorz; Fabris, Bruno; Carretta, Renzo; Benetos, Athanase; Parati, Gianfranco (Journal of hypertension, 2020)
Mean arterial pressure (MAP) is usually calculated by adding one-third of pulse pressure (PP) to DBP. This formula assumes that the average value of pulse waveform is constant in all individuals and coincides with 33.3% of PP amplitude (MAP = DBP + PP × 0.333). Other formulas were lately proposed to improve the MAP estimation, adding to DBP an established percentage of PP: MAP = DBP + PP × 0.40; MAP = DBP + PP × 0.412; MAP = DBP + PP × 0.333 + 5 mmHg. The current study evaluated the integral of brachial pulse waveform recorded by applanation tonometry in 1526 patients belonging to three distinct cohorts: normotensive or hypertensive elderly, hypertensive adults, and normotensive adults. The percentage of PP to be added to DBP to obtain MAP was extremely variable among individuals, ranging from 23 to 58% (mean: 42.2 ± 5.5%), higher in women (42.9 ± 5.6%) than men (41.2 ± 5.1%, P < 0.001), lower in the elderly cohort (40.9 ± 5.3%) than in the general population cohort (42.8 ± 6.0%, P < 0.001) and in the hypertensive patients (42.4 ± 4.8%, P < 0.001). This percentage was significantly associated with DBP (β = 0.357, P < 0.001) and sex (β = 0.203, P < 0.001) and significantly increased after mental stress test in 19 healthy volunteers (from 39.9 ± 3.2 at baseline, to 43.0 ± 4.0, P < 0.0001). The average difference between MAP values estimated by formulas, compared with MAP assessed on the brachial tonometric curve, was (mean ± 1.96 × SD): -5.0 ± 6.7 mmHg when MAP = DBP + PP × 0333; -1.2 ± 6.1 mmHg when MAP = DBP + PP × 0.40; -0.6 ± 6.1 mmHg when MAP = DBP + PP × 0.412; -0.4 ± 6.7 mmHg when MAP = DBP + PP × 0.333 + 5. Due to high interindividual and intraindividual variability of pulse waveform, the estimation of MAP based on fixed formulas derived from SBP and DBP is unreliable. Conversely, a more accurate estimation of MAP should be based on the pulse waveform analysis.